Dermatomyositosis: a rare case report - Behera, Sunil Kumar; Amaravadi, Divya; Alekhya, Merugoju; Sneha, Rakham (International Journal Of Community Medicine And Public Health, 2023)
Dermatomyositis (DM) is a connective tissue disorder and is an idiopathic inflammatory myopathy characterized by skin manifestations. Diagnosis is based on progressive muscle weakness, skin rashes, elevated serum muscle enzymes, muscle biopsy, and abnormal electromyography. In this case study we report a case of classic DM without co-existing malignancy. Timely diagnosis and administration of corticosteroids and physiotherapy led to a better prognosis for the patient. Corticosteroids are the foundation of the treatment. However, the patient remained generally weak and treatment was advised to be continued on discharge.